Pengaruh Tingkat Pendapatan, Sanksi Pajak dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak Umkm Di Wilayah Jakarta Barat - Malvin Agustinus; Eva Oktavini (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2024)
This research aims to examine whether there is a correlation between income levels, tax penalties, and tax rates on the compliance of Micro, Small, and Medium Enterprises (MSME) taxpayers. The population to be studied is MSME taxpayers in the West Jakarta region. Data collection involves primary data in the form of questionnaires. The data analysis method applied in the research is multiple linear regression analysis. The target respondents were 150, but only 123 respondents' data were obtained. MSME participants are predominantly female. Testing the data quality includes validity and reliability tests. The validity and reliability tests result in valid data for all questionnaire items. Additionally, classical assumption tests such as normality test, Glejser test, and multicollinearity test are conducted. Subsequently, hypothesis testing of the data involves F-test, T-test, and coefficient of determination test. The research findings indicate that tax penalties and tax rates significantly influence the compliance of MSME taxpayers, with a percentage value of 50.1% and 49.9%, respectively. Other variables also affect compliance, while income levels do not influence the compliance of MSME taxpayers. Keywords: Income Level, Tax Sanctions, Tax Rates and MSME Taxpayer Compliance